2003
DOI: 10.1099/vir.0.19185-0
|View full text |Cite
|
Sign up to set email alerts
|

The packaging signal of simian immunodeficiency virus is upstream of the major splice donor at a distance from the RNA cap site similar to that of human immunodeficiency virus types 1 and 2

Abstract: The packaging signal of simian immunodeficiency virus is upstream of the major splice donor at a distance from the RNA cap site similar to that of human immunodeficiency virus types 1 and 2 Deletion mutation of the RNA 59 leader sequence of simian immunodeficiency virus (SIV) was used to localize the virus packaging signal. Deletion of sequences upstream of the major splice donor (SD) site produced a phenotype most consistent with a packaging defect when analysed by both RNase protection assay and RT-PCR. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…It is possible that these purine motifs might be involved in the specific RNA-protein interactions taking place during genomic RNA selection and encapsidation. Likewise, deletion mutagenesis studies suggest that an extended SL1 element is involved in encapsidation and dimerization of the SIVmac239 genomic RNA (Strappe et al 2003;Whitney and Wainberg 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these purine motifs might be involved in the specific RNA-protein interactions taking place during genomic RNA selection and encapsidation. Likewise, deletion mutagenesis studies suggest that an extended SL1 element is involved in encapsidation and dimerization of the SIVmac239 genomic RNA (Strappe et al 2003;Whitney and Wainberg 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the case with human immunodeficiency virus, simian immunodeficiency virus, and Mason-Pfizer monkey virus (4,5,9,11), this region folded into several stem-loops, of which four were stable, named stemloops 1 to 4 (SL1 to SL4). Folding of the mutant vector RNAs revealed that most of the conformation of the wild-type UTR was destroyed in the vectors with only 90 and 120 bp of the UTR, except for SL1, which was conserved in all transfer vector RNAs (Fig.…”
mentioning
confidence: 83%
“…Lentiviral vectors derived from HIV-1, HIV-2, and SIVmac251 have been described previously (48)(49)(50)(51)(52). These vectors were originally engineered from NL4-3, ROD, and SIVmac251 viral strains.…”
Section: Methodsmentioning
confidence: 99%